Experimental Study on Properties of Syngas, Tar, and Biochar Derived from Different Gasification Methods - Yang Yue; Xiaoling Jin; Lei Deng (Applied Sciences, 2023)
Biomass gasification technology is a clean and renewable energy utilization approach. Understanding the evolution of gasification product properties is crucial to achieving carbon neutrality goals. A fixed-bed reactor is employed for the biomass gasification with CO2 in this study. Various methodologies have been conducted to characterize the syngas, tar, and biochar produced from the electric gasification (EG) and microwave gasification (MG) of oak and corn stalk samples at different temperatures. When gasifying the same biomass at the same temperature, the syngas yield of MG is generally 3–7% higher than that of EG, and the difference increases with decreasing temperature. The biochar yield of MG is 3–6% higher than that of EG. EG produces more tar at 600–800 °C. The yield of syngas increases as the gasification temperature rises from 600 to 1000 °C, but that of tar and biochar falls. The syngas mainly comprises H2, CH4, CO, and CO2. MG produces 8–15% higher CO content and 2.5–3.5% higher H2 content than EG. This is due to different heating mechanisms. The net calorific value of syngas increases with temperature, reaching a maximum of 11.61 MJ m−3 at 1000 °C for syngas from corn stalk MG. When the temperature rises from 600 to 1000 °C, more primary tars are converted into polycyclic aromatic hydrocarbons (PAHs). At 900 °C, corn stalk biochar from MG has a maximum specific total pore volume (0.62 cm3 g−1), surface area (525.87 m2 g−1), and average pore diameter (4.18 nm). The intensities of the characteristic peaks of biochar functional groups decrease gradually. The heating method has little effect on the types of functional groups.